An Update on Laboratory Diagnostics in Haemophilia A and B - Müller, Jens; Miesbach, Wolfgang; Prüller, Florian; Siegemund, Thomas; Scholz, Ute; Sachs, Ulrich J.; Standing Commission Labor (STAEKOLA) of the Society of Thrombosis and Haemostasis Research (GTH) (Hämostaseologie, 2022)
Haemophilia A (HA) and B (HB) are X-linked hereditary bleeding disorders caused by lack of activity of coagulation factors VIII (FVIII) or IX (FIX), respectively. Besides conventional products, modern replacement therapies include FVIII or FIX concentrates with an extended half-life (EHL-FVIII/FIX). Two main strategies for measuring plasma FVIII or FIX activity are applied: the one-stage clotting assay (OSCA) and the chromogenic substrate assay (CSA), both calibrated against plasma (FVIII/FIX) standards. Due to the structural modifications of EHL-FVIII/FIX, reagent-dependent assay discrepancies have been described when measuring the activity of these molecules. Assay discrepancies have also been observed in FVIII/FIX gene therapy approaches. On the other hand, nonfactor replacement by the bispecific antibody emicizumab, a FVIIIa-mimicking molecule, artificially shortens activated partial thromboplastin time–based clotting times, making standard OSCAs inapplicable for analysis of samples from patients treated with this drug. In this review, we aim to give an overview on both, the currently applied and future therapies in HA and HB with or without inhibitors and corresponding test systems suitable for accompanying diagnostics.
Keywords: haemophilia A/B; factor concentrates; extended half-life products; emicizumab; gene therapy